“THE ECONOMIC IMPORTANCE OF MATHEMATICAL MODELING IN EXPANDING INVESTMENT IN THE CONTEXT OF GLOBALIZATION AND DIGITAL EDUCATION” - Djumayev Adiz Zakirovich; Narzullayeva Feruza Sodiqovna (Scholar Express Journal, 2025)
The article analyzes the theoretical and practical aspects of expanding investment flows in the context of globalization. It examines the factors influencing the investment environment, including the integration of the global financial market, the development of digital technologies, state policy, and the importance of human capital. The economic significance of teaching the subject “Mathematical Modeling” in the digital educational environment is also highlighted. The study demonstrates the potential of mathematical modeling to scientifically explain economic processes, analyze investment projects, and improve their efficiency. The practical achievements of Uzbekistan in investment reforms and the development of digital education are also examined.
Keywords: Globalization; investment; digital education